Diseminasi Optimalisasi Lahan melalui Budidaya Sayuran-Ikan Secara 3-in-1 di Lahan Perkotaan - Benyamin Lakitan; Fitra Fadhilah Rizar; Strayker Ali Muda; Dora Fatma Nurshanti; Rofiqoh Purnama Ria; Fitra Gustiar; Lya Nailatul Fadilah; Andi Wijaya; Siti Nurul Aidifitri (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
The 3-in-1 vegetable-fish cultivation is an innovative cultivation system that integrates floating and climbing vegetable cultivation with fish culture. This cultivation is a solution to the problem of narrow land in urban areas for vegetable-fish cultivation to create: a) Fish farming in a concrete pool at the bottom position, b) Shade-tolerant vegetables cultivated using a floating culture system, and c) Climbing vegetables on a dedicated netted-frames as high as 2 meters above the pool. The dimensions of the pool correspond to the available land. The floating raft was constructed using 69 units of 1.5 L plastic bottles as floaters, assembled into a raft with a surface area of 2 m2. The buoyancy capacity of the raft is 120 kg. The raft has been patented with Granted patent No. IDP 000065141. The community service activities are a) Open demonstrations for 3-in-1 vegetable-fish farming installations; b) Socialization and assistance to communities interested in implementing it; and c) Collection of data and information for evaluation and publication materials. Static demonstration activities during one cycle of cultivation and socialization to three potential community groups, namely: a) Urban communities as the primary target; b) Journalists for more enlarging coverage of the dissemination; and c) Agricultural students for the learning process. Urban communities can adopt the dissemination of land optimization through 3-in-1 vegetable-fish cultivation on urban land. Community interest in this cultivation system innovation is outstanding, as represented by the community's enthusiasm for this program.